Characteristics of symptomatic epilepsy and other neurological disorders in children with lissencephaly - V. I. Guzeva; I. V. Ochrim; V. R. Kasumov; O. V. Guzeva; V. V. Guzeva; N. E. Maksimova (Бюллетень сибирской медицины)
Brain malformations are one of the most frequent causes of epilepsy in childhood. In patients with malformations of the brain epilepsy is diagnosed in 75–80% of cases. Lissencephaly is a cortical malformation, which develops as a result of global violations of glial-neuronal migration. The probable cause of the deterioration is considered to be the “Transportation” function-specific astrocytes and radial glial fibers involved in the migration of germ cells. The absence of convolutions in the mature brain – morphological substrate is agyria full lissencephaly, the presence of only a single, rudimentary and thickened gyri (pachygyria) – incomplete lissencephaly. Clinical manifestations lissencephaly presented delayed psycho-motor development, spastic tetraplegia and intractable epilepsy.Materials and methods. To examine and compare the clinical, electrophysiological and neuroimaging results in children with symptomatic epilepsy with lissencephaly, to assess the effectiveness of antiepileptic therapy and to identify the frequency of drug-resistant forms of epilepsy. The study involved 22 patients with lissencephaly. In all the children studied anamnesis and neurological examinations were conducted and neuroimaging and electrophysiological studies were performed.Results. In neuroimaging examinations, pachygyria and agyria were equally identified. The preferential localization pachygyria was observed in the frontal region. In most cases, clinical examination revealed the presence of motor deficits, cognitive and behavioral disorders. The debut of seizures was observed significantly more often in the age of six months. In general, during the observation period focal seizures with secondary generalization like, with or without secondary generalization were more common. Neuroimaging and EEG correlation was noted in half of the children surveyed.Conclusions. In the treatment of epileptic seizures in patients valproate are used more often. The results of the study suggest that one of the common causes of severe forms of epilepsy in children is malformations of brain development, so their early diagnosis and adequate antiepileptic therapy correlated with the prevention pharmacoresistance, symptomatic epilepsy and disability in children.